Robust single allocation p-hub median problem under hose and hybrid demand uncertainties: models and algorithms. Issue 3 (2nd July 2020) - Ghaffarinasab, Nader; Zare Andaryan, Abdullah; Ebadi Torkayesh, Ali
ABSTRACT: Hub location problem is one of the extensively studied and important problems in the field of facility location and network design with numerous applications in transportation, postal services, and telecommunications. In this paper, we address the robust single allocation p -hub median problem under polyhedral demand uncertainty. The origin-destination (O/D) flow values are assumed to be uncertain and are modeled as two different polyhedral uncertainty sets, called the hose and the hybrid uncertainty sets. The problems are formulated as linear MIP models and matheuristic solution algorithms based on Tabu Search (TS) are developed for solving them. Computational experiments show the capability of the proposed algorithms to solve the real-world instances of the problem in small computational times. Furthermore, the effect of different input parameters on the final solutions are studied.